Organotypic culture system for prepubertal mice testicular tissue: A comparative study - Deng, Liping; Wang, Xinyi; Wu, Xunwei; Zhou, Hui; Cheng, Yintao; Li, Honggang (Frontiers in Endocrinology, 2025)
BackgroundPrepubertal testicular organotypic culture serves as an in vitro model for research in regenerative medicine, developmental biology, and toxicology. However, the selection of culture systems for diverse applications and purposes lacks explicit rationale or standardized guidelines.ObjectiveTo evaluate the developmental status of germ cells and Sertoli cells in prepubertal testicular organotypic cultures using different media and tools, and to provide evidence for model standardization.Materials and MethodsImmature testicular tissues (ITTs) were isolated from prepubertal mice and cultured in combinations of three media (Medium 1/2/3, M1/2/3) and two tools (agarose gel pillars, tissue culture inserts) at 34°C with 5% CO₂ for 8 days. After culture, tissue morphology and cell status were assessed via histological analysis (hematoxylin-eosin [HE] staining) and immunofluorescence. Quantification was performed using ImageJ, and statistical analysis was conducted with GraphPad Prism.ResultsOver the 8-day culture period, ITTs survived and grew in all systems, maintaining the structural integrity of seminiferous tubules, with tubular diameter increasing over time. Spermatogonia remained viable within the tubules, the number of germ cells increased, and both germ cells and spermatogonia exhibited proliferative activity. Sertoli cells were well preserved, and spermatogonia differentiated into meiotic spermatocytes in the tubule lumen. Compared with M1, M2 and M3 significantly enhanced the proliferation rates of germ cells and spermatogonia, with M2 showing the highest efficiency. Notably, M2 yielded the greatest number of differentiated spermatocytes, whereas M1 better preserved spermatogonial populations despite its lower proliferation rate.ConclusionThis study clarifies the differential effects of culture systems on the development of germ cells and Sertoli cells in ITTs, and provides a standardized organotypic platform for investigating spermatogenesis, male infertility, and potential therapeutic interventions.